Decline in Pneumococcal Disease Attenuated in Older Adults and Those With Comorbidities Following Universal Childhood PCV13 Immunization. (20th September 2018) - Pelton, Stephen I; Bornheimer, Rebecca; Doroff, Robin; Shea, Kimberly M; Sato, Reiko; Weycker, Derek
Abstract: Background: Following introduction of 7-valent pneumococcal conjugate vaccine (PCV7) in the United States, epidemiology of pneumococcal disease shifted such that disease incidence in the elderly exceeded that in children. We evaluated the impact of replacing PCV7 with PCV13 on disease burden in adults and identified age/risk-specific subgroups with the highest remaining disease burden. Methods: A retrospective design and data from two US healthcare claims repositories were used. Study population included adults aged ≥18 years and was stratified by age (18–49, 50–64, 65–74, ≥75) and risk profile (healthy, at-risk, high-risk). Rate ratios comparing invasive pneumococcal disease (IPD), all-cause hospitalized pneumonia (ACHP), and pneumococcal pneumonia requiring hospitalization among at-risk and high-risk adults vs healthy counterparts were estimated for 2007–2010 (pre-PCV13), 2011–2012 (peri-PCV13), and 2013–2015 (post-PCV13). Results: Across study periods, IPD and ACHP rates increased with age (2–27 times higher in persons ≥75 vs 18–49) and comorbidity (4–20 times higher in high-risk vs healthy). From pre- to post-PCV13 period, IPD rates declined 5%–48% and ACHP rates declined 4%–19% across age and risk groups (ACHP did not decline in persons ≥75). Decline in IPD and ACHP was attenuated among older adults and those with comorbidities. Accordingly, rate ratios among at-risk and high-risk persons (vs healthy counterparts) increased during the peri- and post-PCV13 periods compared with the pre-PCV13 period. Conclusions: The switch to PCV13 was associated with large declines in pneumococcal disease among US adults. However, the decline was attenuated with increasing age (and, for ACHP, was absent in persons ≥75) and in those with comorbidities. Abstract : Declining incidence of invasive pneumococcal disease and all-cause pneumonia following introduction of 13-valent pneumococcal conjugate vaccine for children was observed in adults aged ≥18 years. However, decline varied by age and comorbidity profile, with smaller reductions in older individuals and those with comorbidity.